Efektivitas Terapi Akupunktur pada Pasien Osteoarthritis Lutut : Literature Review - Tarigan, Gladys Ametha; Ahmad Fauzi; Anisa Nuraisa Jausal (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Knee osteoarthritis is a degenerative disease that causes stiffness, pain, and joint deformity, potentially impacting patients' quality of life. Acupuncture is a non-pharmacological therapy option. This study aimed to evaluate the effectiveness of acupuncture therapy in knee osteoarthritis patients using literature searches on PubMed®, Cochrane®, and ScienceDirect® with the keyword